Assessment of Pain and Trismus and Determining the Difficulty Level of Tooth Extraction with Modified Parant Scale - Agrawal, Manish; Rahman, Quazi Billur; Naulakha, Deependra; Karki, Riwaj (Birat Journal of Health Sciences, 2018)
Introduction: Third molar extraction is the most commonly performed procedure by oral and maxillofacial surgeons and most of the extraction leads to minimum pre and post operative difficulties if proper preoperative planning is done and if surgical principles are strictly followed. Objective: This study evaluated whether pre and post operative pain and trismus were related to difficulty of surgery. Methodology: Total number of patients included in this study were 266 (male 135 and female 131), age range from 18 to 34 years. Preoperative diagnosis was made by clinical examination and radiographs. Clinical examination was done to determine pain, swelling and mucosal coverage of tooth whereas OPG and RVG were taken to assess the angulations, level of tooth impaction and bony coverage of tooth. Standardized technique was used for tooth extraction; buccal guttering, adequate elevation, reflection of mucoperiosteal flap, crown sectioning and ostectomy. Evaluation of pain and trismus was done preoperatively, on first and third post operative day. SPSS version 16 was used to analyse the data. Chi square (x²) test and unpaired ’t’ test were done. Modified Parant Scale was used to evaluate the difficulty of tooth extraction; Group I: forceps extraction; Group II: ostectomy; Group Ill: ostectomy and crown sectioning; Group IV: difficult extraction. Results: When both preoperative and postoperative results were compared after data analysis, pain was significantly reduced and significant inter incisal opening was achieved, in both the groups P > 0.05. The results were statistically not significant. Conclusion: Postoperative pain and trismus was minimum in (Group I) then in (Group II to IV). The incidence of postoperative pain and trismus among all the groups were more or less similar. Hence, no significant difference was found. Birat Journal of Health Sciences Vol.2/No.3/Issue 4/Sep- Dec 2017, Page: 282-286